42b+7b^2-b^2+b+20=0
6b^2+43b+20=0
D=1849-480=1369
b1=(-43-37)/12=-6.6666
b2=(-b+37)/12=0,5
Выражение: 7*b*(6+b)-(b-5)*(b+4)
ответ: 43*b+6*b^2+20
Решаем по действиям:
1) 7*(6+b)=42+7*b
2) (42+7*b)*b=42*b+7*b^2
3) (b-5)*(b+4)=b^2-b-20
4) 42*b+7*b^2-(b^2-b-20)=42*b+7*b^2-b^2+b+20
5) 7*b^2-b^2=6*b^2
6) 42*b+b=43*b
Решаем по шагам:
1) (42+7*b)*b-(b-5)*(b+4)
2) 42*b+7*b^2-(b-5)*(b+4)
3) 42*b+7*b^2-(b^2-b-20)
4) 42*b+7*b^2-b^2+b+20
5) 42*b+6*b^2+b+20
6) 43*b+6*b^2+20
42b+7b^2-b^2+b+20=0
6b^2+43b+20=0
D=1849-480=1369
b1=(-43-37)/12=-6.6666
b2=(-b+37)/12=0,5
Выражение: 7*b*(6+b)-(b-5)*(b+4)
ответ: 43*b+6*b^2+20
Решаем по действиям:
1) 7*(6+b)=42+7*b
2) (42+7*b)*b=42*b+7*b^2
3) (b-5)*(b+4)=b^2-b-20
4) 42*b+7*b^2-(b^2-b-20)=42*b+7*b^2-b^2+b+20
5) 7*b^2-b^2=6*b^2
6) 42*b+b=43*b
Решаем по шагам:
1) (42+7*b)*b-(b-5)*(b+4)
2) 42*b+7*b^2-(b-5)*(b+4)
3) 42*b+7*b^2-(b^2-b-20)
4) 42*b+7*b^2-b^2+b+20
5) 42*b+6*b^2+b+20
6) 43*b+6*b^2+20